Multivariate density estimation for interval‐censored data with application to a forest fire modelling problem. Issue 6 (15th June 2016) - Braun, W. J.; Stafford, J. E.
Abstract : Local likelihood‐based density estimation methods are developed for multivariate interval‐censored data. An extension of the Nadaraya–Watson local regression estimator to the interval‐censored data context arises in a natural way. The conditional density estimation scheme is used to study the holdover distribution of lightning‐caused wildfire ignitions in Northern Ontario. Copyright © 2016 John Wiley & Sons, Ltd.